(untitled) (Nigerian Journal of Physiological Sciences, 2022)
Alzheimer’s disease (AD) is the most common cause of dementia that affects one patient every seven seconds, with over 35 million people currently affected worldwide. The aim of the study was to investigate the modulation of memory and neurochemical responses by resveratrol and environmental enrichment (EE) in aluminium chloride (AlCl3) model of Alzheimer’s disease in mice. Male mice used for the study were divided into nine groups, of seven animals each. Group I (negative control): 0.2 ml normal saline/kg, Group II: 0.2 ml CMC/kg. Group III: resveratrol (200 mg/kg/), Group IV: CMC and kept in EE, Group V: AlCl3 at dose of 50 mg/kg, Group VI: resveratrol at dose of 200 mg/kg and kept in EE, Group VII: AlCl3 (50 mg/kg) + resveratrol (200 mg/kg), Group VIII: AlCl3 (50 mg/kg) and kept in EE, Group IX: AlCl3 (50 mg/kg) + resveratrol (200 mg/kg) and kept in enriched environment. All treatments were oral and lasted for 8 weeks. Assessments of memory was carried out before treatment, and at weeks 4 and 8, after the first treatment. The mice were sacrificed and hippocampal samples collected for neurochemical analysis. The findings of the study suggest that AlCl3 induced contextual fear memory deficit over time (p < 0.05), which was improved by resveratrol. Both Aβ and Nrf2 significantly (p < 0.05) increased in AlCl3 + EE + resveratrol group. In conclusion, Individual treatment with either resveratrol or EE improved memory over the combined treatment in AlCl3 model of AD by decreasing Aβ protein concentration.